Perubahan Warna Sosis Ayam Fermentasi Dengan Penambahan Nitrit dan Lactobacillus fermentum BR 17 - Roisu Eny Mudawaroch; Setiyono Setiyono; Lies Mira Yusiati; Edi Suryanto (Jurnal Riset Agribisnis dan Peternakan, 2018)
The purpose of this study was to determine the color change of fermented chicken sausage with the addition of nitrite and Lactobacillus fermentum BR 17. The treatment in this study was fermented chicken sausage with additives: nitrite, Lactobacillus fermentum BR 17, and Lactobacillus fermentum BR 17 + nitrite. The parameters observed in this study were color intensity and color appearance of fermented chicken sausage. This study uses a Split Plot Design with the main plot of nitrite and Lactobacillus fermentum BR 17 and an old plot of manufacture. The results of the study were additives in fermented chicken sausage which had no significant effect on the value of b * (yellowish). The value of b * in Nitrit fermented chicken sausage, Lactobacillus fermentum BR 17, and Lactobacillus fermentum BR 17 + nitrite were 7.19; 6.74; and 7.09. The length of time for fermented chicken sausage production has a very significant effect on the b * value. The fermented chicken sausage b * value at the beginning was 7.59 and decreased to 6.13 at the end of manufacture. The results of the analysis of the additives in fermented chicken sausage have a very significant effect on the value of a * (redness). A * values ​​in nitrite fermented chicken sausage, Lactobacillus fermentum BR 17, and Lactobacillus fermentum BR 17 + nitrite respectively 5.29; 4.99; and 4.51. The results of a variety of analyzes on the duration of making fermented chicken sausage gave a very significant effect on the value of a *. The a * fermented chicken sausage value at the beginning was 4.97 and rose to 5.25 on the 3rd day of fermentation and then decreased during drying to 4.43 at the end of manufacture. The results of the analysis of the additives in fermented chicken sausage have a very significant effect on the L * value (brightness). L * value in nitrite fermented chicken sausage, Lactobacillus fermentum BR 17, and Lactobacillus fermentum BR 17 + nitrite respectively 38.50; 43.71; and 39.84. The results of the analysis of variance in the duration of manufacture of fermented chicken sausage have a very significant effect on the value of L * (brightness). The value of L * fermented chicken sausage at the beginning was 54.05 and decreased to 29.54 at the end of manufacture. The color of fermented sausage with nitrite and Lactobacillus fermentum BR 17 and the different preparation times showed the difference between the additive used and the length of time to make fermented sausage. The conclusion of this research is that the additive used does not affect the value of *b and has a very significant effect on the value of * a and * L. the time for making fermented chicken sausage has a significant effect on the value of * b and a very significant effect on the value of a * and * L. The appearance of fermented chicken sausage shows the difference as well as the